Introduction to the Special Issue “Political economic perspectives of the Israeli-Palestinian Conflict” - Miaari, Sami H.; Calì, Massimiliano (Taylor and Francis, 2021)
The Israeli-Palestinian conflict is the world’s most protracted contemporary conflict and one which has gained international prominence throughout the years. As a result of the Six Days War in 1967, the West Bank and the Gaza Strip fell under Israeli control. The conflict has evolved through ebbs and flows of violence including two Palestinian uprising against Israeli control (the First and Second Intifada). These have led to tens of thousands of Palestinian and thousands of Israeli victims. There is a growing theoretical and empirical literature analyzing the Israeli-Palestinian conflict. In this review, we discuss a selected number of studies that are most closely related to the topics covered by the articles in this special issue.